Diseño de mezcla de concreto translúcido aplicando agregados que permiten el paso de luz, Lima – 2021 - Prado Ñaupa, Diane Ethel (2022)
The objective of this work is to carry out a mix design for translucent concrete using aggregates that allow the passage of light, therefore, an analysis related to the translucent concrete mix design was carried out, in a time interval of 10 years, to define what type of aggregates, additives and w/c ratio, are the ones that will provide the greatest benefit to the final product. For this, a mix design for translucent concrete was proposed, referring to ACI 211.1, since different aggregates such as tempered glass, quartz, white cement and also a plasticizing additive will be used to obtain an optimal design for translucent concrete. In addition, application cases with additive were carried out, in order to obtain different mix designs with the properties of translucency and resistance to compression, with these designs it was concluded that quartz and Ottawa sand are the aggregates that most favor the passage of light, however, using glass at 40% and quartz at 60% in the mix design gives moderate translucency to the mix, finally it was defined that the possible applications of this type of concrete are given for glass block type partitions and false ceiling , that is, for non-bearing aesthetic structures.